2021
DOI: 10.1177/00048674211044639
|View full text |Cite
|
Sign up to set email alerts
|

Using the Patient Health Questionnaire to estimate prevalence and gender differences of somatic symptoms and psychological co-morbidity in a secondary inpatient population with abdominal pain

Abstract: Background: Somatic disorders and somatic symptoms are common in primary care populations; however, little is known about the prevalence in surgical populations. Identification of inpatients with high somatic symptom burden and psychological co-morbidity could improve access to effective psychological therapies. Methods: Cross-sectional analysis ( n = 465) from a prospective longitudinal cohort study of consecutive adult admissions with non-traumatic abdominal pain, at a tertiary hospital in New South Wales, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This non-validated self-reported questionnaire was used to record pre-admission healthcare utilization, which was reliant on participant recollection. Although non-validated, the responses of the patients were tested by a comprehensive chart review for a representative sample of the cohort, which showed that the patients’ recollection of their attendance at hospital, and their use of hospital-based tests, was very accurate 35 . The MBS was used to estimate health expenditure, as this is the national standard in Australia; however, this is not comparable to Diagnosis Related Groups or Casemix used in other countries, and thus international comparisons must be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…This non-validated self-reported questionnaire was used to record pre-admission healthcare utilization, which was reliant on participant recollection. Although non-validated, the responses of the patients were tested by a comprehensive chart review for a representative sample of the cohort, which showed that the patients’ recollection of their attendance at hospital, and their use of hospital-based tests, was very accurate 35 . The MBS was used to estimate health expenditure, as this is the national standard in Australia; however, this is not comparable to Diagnosis Related Groups or Casemix used in other countries, and thus international comparisons must be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A cross‐sectional study of consecutive adult patients admitted to the Acute General Surgical Unit (AGSU) with any form of non‐traumatic abdominal pain. Full details of the study and the participant characteristics have been reported previously 4 …”
Section: Methodsmentioning
confidence: 99%
“…Full details of the study and the participant characteristics have been reported previously. 4 Exclusion criteria: age less than 18 years, inability to provide informed consent; or any patient admitted to other services such as general medicine. Only the index admission in the study period was used for analyses.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations